Endoscopic Evaluation and Treatment of Postoperative Bariatric Surgery Complications. (December 2017) - Docimo, Salvatore; Svestka, Michael
The number of patients undergoing bariatric surgery continues to increase. The American Society for Metabolic and Bariatric Surgery (ASMBS) estimates the number of bariatric surgical procedures performed increased from 158 000 in 2011 to 190 000 in 2015. Concurrently, the incidence of postoperative complications specific to bariatric patients will inevitably increase as well. Endoscopic evaluation of postoperative bariatric patients and endoscopic interventions are rapidly evolving. We present a review of the postoperative anatomy of bariatric patients, what complications to expect, and treatment options.